2020
DOI: 10.1136/bmj.m2942
|View full text |Cite
|
Sign up to set email alerts
|

Personal use of permanent hair dyes and cancer risk and mortality in US women: prospective cohort study

Abstract: ObjectiveTo evaluate the associations between personal use of permanent hair dyes and cancer risk and mortality.DesignProspective cohort study.Setting and participants117 200 women enrolled in the Nurses’ Health Study, an ongoing prospective cohort study of female nurses in the United States. The women were free of cancer at baseline, reported information on personal use of permanent hair dyes, and were followed for 36 years.ExposureStatus, duration, frequency, and integral use (cumulative dose calculated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…Apart from heavy metals such as Hg and Pb, a variety of established toxic chemicals are still being used as common ingredients in cosmetics, which are prohibited by many countries. For example, it is well established by earlier research studies that some hair dyes and cosmetics have a potential role in inducing carcinogenesis [50].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from heavy metals such as Hg and Pb, a variety of established toxic chemicals are still being used as common ingredients in cosmetics, which are prohibited by many countries. For example, it is well established by earlier research studies that some hair dyes and cosmetics have a potential role in inducing carcinogenesis [50].…”
Section: Discussionmentioning
confidence: 99%
“…The null association for adolescent hair dye use is largely consistent with previous studies of adult hair dye which have suggested that any hair dye-associated risks with overall breast cancer may be small. [21][22][23][24][25][26][27]42 However, most, but not all, of these studies have been conducted in predominately white study populations; therefore, these findings may not be applicable to black women.…”
Section: Discussionmentioning
confidence: 99%
“…Women in our cohort would have been between the ages of 10 and 13 years between 1939 and 1987 and thus the findings presented here represent exposure to products during this time. Although some of the main constituents of hair products appear to be relatively stable over time, 42,43 formulations have changed 44 and would vary by brand. As such, we are unable to identify specific chemical constituents which may be contributing to risk.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, it has been demonstrated that the use of synthetic hair colorants increases the risk of basal cell carcinoma, breast cancer and ovarian cancer. 22 However, minor progress has been made to avoid such defects of synthetic hair dyes. 21,23,24 During the past decade, nanotechnology has provided novel approaches for new types of hair dyes.…”
Section: Introductionmentioning
confidence: 99%